Biome Awareness Disparity is BAD for tropical ecosystem conservation and restoration - Silveira, Fernando A. O.; Ordóñez-Parra, Carlos A.; Moura, Livia C.; Schmidt, Isabel B.; Andersen, Alan N.; Bond, William; Buisson, Elise; Durigan, Giselda; Fidelis, Alessandra [UNESP]; Oliveira, Rafael S.; Parr, Catherine; Rowland, Lucy; et al. (Wiley, 2021)
We introduce the concept of Biome Awareness Disparity (BAD)—defined as a failure to appreciate the significance of all biomes in conservation and restoration policy—and quantify disparities in (a) attention and interest, (b) action and (c) knowledge among biomes in tropical restoration science, practice and policy. By analysing 50,000 tweets from all Partner Institutions of the UN Decade of Ecosystem Restoration, and 45,000 tweets from the main science and environmental news media world-wide, we found strong disparities in attention and interest relative to biome extent and diversity. Tweets largely focused on forests, whereas open biomes (such as grasslands, savannas and shrublands) received less attention in relation to their area. In contrast to these differences in attention, there were equivalent likes and retweets between forest versus open biomes, suggesting the disparities may not reflect the views of the general public. Through a literature review, we found that restoration experiments are disproportionately concentrated in rainforests, dry forests and mangroves. More than half of the studies conducted in open biomes reported tree planting as the main restoration action, suggesting inappropriate application of forest-oriented techniques. Policy implications. We urge scientists, policymakers and land managers to recognise the value of open biomes for protecting biodiversity, securing ecosystem services, mitigating climate change and enhancing human livelihoods. Fixing Biome Awareness Disparity will increase the likelihood of the United Nations Decade on Ecosystem Restoration successfully delivering its promises.
Keywords: afforestation; decolonisation; open ecosystems; public perception; reforestation; research bias; savannas; tree planting